(untitled) (Islas, 2023)
Introduction: This article has two objectives. The first is to present the sociolinguistic factors that have conditioned the conformation and use of the Creole language spoken in the Caribbean Island of St. Lucia (LCSL), and the second is to examine the structural aspects: phonic and grammatical aspects that constitute descriptive gaps in the linguistic studies of this Creole. Methods: In the description and explanation of linguistic forms and categories, methods of structural analysis by levels have been taken into account, particularly those related to phonological and morphosyntactic analysis. This study also shows a comparison between phonic and grammatical structures of English, French and St. Lucia Kwéyòl. Results: Kwéyòl is the language spoken by a large majority of the population and the language used for everyday communication in the Saint Lucian community. The proposed analysis identifies phonological and morphosyntactic patterns evidenced by examples obtained from native speakers of the language. Conclusions: The minimal phonology and grammatical aspects we have presented here point out that LCSL has a structure of its own and constitutes a system independent of French.